Trimerization of 1,2‐Diaminocyclohexane Catalyzed by a Metal–Organic Cage Tandem Catalyst with Dual Biomimetic Active Sites - Xiao‐Jun Chai; Zhu Zhuo; Zi‐Ang Nan; Shiqiang Mu; Zhong‐Yu Peng; Ting Chen; Wei Wang; Li‐Feng Lin; Xi Meng; Mao‐Chun Hong; You‐Gui Huang (Advanced Science, 2025)
Abstract Cascade reactions that form multiple chemical bonds in one synthetic step are important for the synthesis of complex molecules. Molecular catalysts for cascade reactions generally require two or more catalytic centers, yet anchoring distinct catalytic centers onto a single molecular catalyst remains extremely challenging. Here a metal–organic cage (MOC) [(ClO4)2@Zn20(L)8(HCO2)6(OH)6(H2O)8]2+ (Zn20‐MOC) (H3L = tris(2‐benzimidazolylmethyl)amine) carrying dual biomimetic active sites is reported, i.e. mononuclear {ZnII(L)(H2O)} and dinuclear {L2ZnII(CHO2)(OH)ZnIIL2}. The two active sites play different roles in the catalytic cascade trimerization of 1,2‐diaminocyclohexane 1), which produces hexadecahydro‐5a,11a‐butanoquinoxalino[2,3‐b]quinoxaline 2) with a yield of ≈71.32%. It is find that the mononuclear {ZnII(L)(H2O)} site catalyzes the dimerization reaction of 1, yielding an intermediate product 1,2,3,4,4a,6,7,8,9,10a‐decahydrophenazine (inter. 4). Further reaction between 1 and inter. 4 to form the final product must be catalyzed by the dinuclear {L2ZnII(HCO2)(OH)ZnIIL2} site. This work not only provides a new approach to designing catalysts for cascade reactions, but also develops a unique synthetic strategy for the trimerization of 1,2‐diaminocyclohexane, a process that has been unexplored until now.